Dam break flood inundation modelling for Klang gate dam - Zainal Abidin, Nurashikin (2015)
Dams play a very vital role in the economy of a country by providing essential benefits like irrigation, hydropower, flood control and mitigation, drinking water and recreation. However in the unlikely and rare event of their failure, these may cause catastrophic flooding in the downstream area which may result in huge loss and damage to human life and property. In Malaysia, we have not had the experience of any such dam failures. However as the dams in the country get older, we cannot avoid but to face the reality that we have to take notice of the conditions of these dams from the safety point of view. This project report presents flood inundation mapping due to dam break of Klang Gate Dam. The Klang Gate Dam were modelled using a HEC-RAS one-dimensional hydraulic model to capture the hydraulic response of the river and its floodplains in extreme flooding condition due to dam break. Klang Gate Dam has been chosen as the study area where the dam has been classified as a significant high hazard. The purpose of this study is to determine maximum inundation depth of the flood waves, peak discharge and flood wave arrival time at various locations of the downstream valley and to develop flood inundation map depending on the severity of the flood in event of the failure of the Klang Gate Dam by using HEC-RAS. A steady flow HEC-RAS Model is developed for a probable maximum flood (PMF) failure for overtopping mode and the breach parameter of possible worst case scenario were considered in the study. The result showed that the peak discharge due to overtopping failure is 21,272 m3/s with possible maximum velocity of 12 m/s. The result indicated that impact of breach outflow to the downstream area is significant. The finding, could benefit authorities or dam owner in an emergency response plans to prevent catastrophic damage at downstream in case of a dam break occurs.